THE TYPOLOGICAL APPROACH TO SUBMARINE GROUNDWATER DISCHARGE (SGD) - Bokuniewicz H.; Buddemeier R.; Maxwell B.; Smith C. (My University, 2003)
Coastal zone managers need to factor submarine groundwater discharge (SGD) in their integration. SGD provides a pathway for the transfer of freshwater, and its dissolved chemical burden, from the land to the coastal ocean. SGD reduces salinities and provides nutrients to specialized coastal habitats. It also can be a pollutant source, often undetected, causing eutrophication and triggering nuisance algal blooms. Despite its importance, SGD remains somewhat of a mystery in most places because it is usually unseen and difﬁcult to measure. SGD has been directly measured at only about a hundred sites worldwide. A typology generated by the Land–Ocean Interaction in the Coastal Zone (LOICZ) Project is one of the few tools globally available to coastal resource managers for identifying areas in their jurisdiction where SGD may be a confounding process. (LOICZ is a core project of the International Geosphere=Biosphere Programme.) Of the hundreds of globally distributed parameters in the LOICZ typology, a SGD subset of potentially relevant parameters may be culled. A quantitative combination of the relevant hydrological parameters can serve as a proxy for the SGD conditions not directly measured. Web-LOICZ View, geospatial software then provides an automated approach to clustering these data into groups of locations that have similar characteristics. It permits selection of variables, of the number of clusters desired, and of the clustering criteria, and provides means of testing predictive results against independent variables. Information on the occurrence of a variety of SGD indicators can then be incorporated into regional clustering analysis. With such tools, coastal managers can focus attention on the most likely sites of SGD in their jurisdiction and design the necessary measurement and modeling programs needed for integrated management.
Keywords: Submarine groundwater; Shallow coastal ecosystem; Land-sea interface; Submarine springs